Thrombosis on a left atrial appendage occluder device: the double-edged sword of stroke prevention strategies in atrial fibrillation. Issue 11 (November 2017) - Ciconte, Giuseppe; Conti, Manuel; Baldi, Mario; Saviano, Massimo; Vicedomini, Gabriele; Pappone, Carlo
Abstract : N/A: A huge thrombus, developing after percutaneous left atrial appendage occlusion, has been successfully treated with dabigatran and aspirin as combination therapy. Although novel oral anticoagulants alone may be effective in thrombus dissolution, the association of an antiplatelet drug may safely enhance this process.